Concerns regarding the effects of the COVID19 pandemic on children health (One Health & Risk Management, 2021)
Introduction. The unexpected situations (lockdown, online school, social distancing) introduced from March 2020 to stop the spread of COVID-19 in most countries worldwide, have affected every citizen. Currently, after more than a year and a half, one of the most affected categories are the children. There is growing concern among researchers about the pandemic impact on the physical, mental development and health of children.Material and methods. A quantitative research was conducted among parents and their children from a gymnasium school in Bucharest regarding the way they perceive how the pandemic restrictions changed their habits. The research methods used were online, using questionnaires created and applied through Google forms. No sample methods could be applied and about 40% of them responded in pairs parent-child. Results. The results showed that the impact of online schooling is not only about the learning effectiveness, but mostly related to the health and development of children who are at risk from the increased time spent on the Internet. Health issues like sedentary lifestyle, obesity, vision and posture impairment, spine problems have increased, being doubled by psychical and mental disorders: stress, isolation, anxiety, depression, lack of attention and concentration, as well as an increase in the number of children exposed to cyberbullying and other online risks. Conclusions. The study analysis showed that there are differences between parents and children's perceptions of the collateral side effects of the pandemic both on physical and mental health of children.
Keywords: COVID19 pandemic restrictions; online school; children physical and psychical/mental health.